Left scapulothoracic dissociation with floating shoulder and grade IIIC open left clavicle fracture with Ideberg type III scapula fracture: a rare case report - Yohannes Sugiarto; Andri Ruliananto Winoto; Muhammad Ali Shodiq (DiscoverSys Inc., 2021)
Background: A high-energy trauma can cause fractures involving clavicle, scapula, and scapulothoracic dissociation with floating shoulder and vascular injuries. Early and correct diagnosis of fracture with vascular injury should be performed to prevent the patient from mortality. This case report aims to evaluate the left scapulothoracic dissociation with floating shoulder and grade IIIC open left clavicle fracture with Ideberg type III scapula fractureCase Presentation: A 19 years old male was on a motorcycle-truck accident which was diagnosed with a rare left scapulothoracic dissociation with floating shoulder and grade IIIC open left clavicle fracture with Ideberg type III scapula fracture. The patient underwent arteriography, repair of the vascular injury, and open reduction internal fixation for the fracture.Conclusion: A rare and complex case of scapulothoracic dissociation with floating shoulder and traumatic subclavian artery injury and clavicle with scapula fractures require early recognition and a multi-disciplinary approach to manage the injuries.